Effect of cooking and smoking methods on proximate composition, lipid oxidation and mineral contents of Polypterus bichir bichir fish from far-north region of Cameroon - Noel Tenyang; Ludovine Ateufack Mawamba; Roger Ponka; Abazidi Mamat; Bernard Tiencheu; Hilaire Macaire Womeni (Heliyon, 2022)
The objective of this study was to evaluate the effect of different cooking and smoking treatments on proximate composition, lipid quality and mineral content of Polypterus bichir bichir, a fish consumed in Far-North Region of Cameroon. Results revealed that the proximate composition was significantly (P < 0.05) affected by treatments: except boiling, all the others treatment reduced significantly (P < 0.05) moisture content of fish while lipid and protein were significantly increased. After processing, the free fatty acids, peroxide and thiobarbituric acid reactive substances values (TBARS) were increased. Iodine value of all treated samples was significantly (P < 0.05) decreased. The combined treatments (frying + boiling and smoking + boiling) negatively affected the lipid quality of fish. Boiling caused significant losses in the mineral contents of fish while smoking treatment led to an important increase of its mineral contents. Steaming appeared to be the best processing method for cooking fish concerning the lipid stability.